The Effect of Problem Based Learning (PBL) Method on Students’ Critical Thinking Ability in Fifth Grade Science Learning in Elementary Schools (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2022)
This research was conducted in elementary schools to determine the effect of the PBL method on the critical thinking skills of fifth grade elementary school students using the PBL method in science subjects. In this study with a population consisting of 59 fifth grade elementary school students, the sample in this study was divided into 2 classes. A few of them; First, the experimental class. Second, the control class. The sampling technique used is a non-probability sampling technique. The design of this study used a posttest only design. In this study, the data collection process used 10 essay questions, the validity test used the product moment formula as many as 10 essay questions with the results of 8 valid questions and 2 drop questions. To test the reliability using Cronbach’s alpha. Data analysis using t-test proves that the value of t_count is greater than t_table 3,645 > 2,002, this research can be concluded that “there is the thinking ability of fifth grade elementary school students in science subjects by applying the Problem-based method (PBL) method”.